Effects of Boron on the Microstructure, Ductility-dip-cracking, and Tensile Properties for NiCrFe-7 Weld Metal. Issue 12 (December 2015) - Mo, Wenlin; Hu, Xiaobing; Lu, Shanping; Li, Dianzhong; Li, Yiyi
Abstract : The distribution of boron and the microstructure of grain boundary (GB) precipitates ( M 23 (C, B)6 and M 2 B) have been analyzed with their effects on the susceptibility of ductility-dip-cracking (DDC) and tensile properties for NiCrFe-7 weld metal, using optical microscopy (OM), secondary ion mass spectroscopy (SIMS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The results show that boron segregates at GBs in NiCrFe-7 weld metal during the welding process. The segregation of boron at GBs promotes the formation of continuous M 23 (C, B)6 carbide chains and M 2 B borides along GBs. The addition of boron aggravates GB embrittlement and causes more DDC in the weld metal, by its segregation at GBs presenting as an impurity, and promoting the formation of larger and continuous M 23 (C, B)6 carbides, and M 2 B borides along GBs. DDC in the weld metal deteriorates the ductility and tensile strength of the weld metal simultaneously.